Analisis Tindak Tutur Direktif dalam Video Pembelajaran Bahasa Indonesia pada Kanal YouTube Kejarcita - Alliya Setiawan Putri; Nurul Hikmah; Narista Amellea Dinata; Najwa Sakinah; Cynara Rahmania; Asep Purwo Yudi Utomo; Satsya Yoga Baswara; Ermawati Ermawati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Learning media is one of the keys to achieving success in the learning process in the classroom. This research aims to obtain, examine, and discuss several utterances in Indonesian language learning videos on the Kejarcita YouTube channel. This research uses a methodological approach (qualitative approach) and a theoretical approach in the form of pragmatics (directive speech acts). The data source for this research was obtained from videos in the "SMP Bahasa Indonesia" playlist uploaded to social media, namely YouTube, from December 2022 to September 2024 on the Kejarcita YouTube channel. This research discusses directive speech acts in junior high school Indonesian language learning videos on the Kejarcita YouTube channel. There are 23 directive speech acts on the Indonesian Middle School playlist Kejarcita YouTube channel. The author groups the data into five subchapters according to the type of directive speech act. It is hoped that the results of this research will provide additional knowledge and can be used as learning reference material for readers, especially in pragmatic studies.